Factors Affecting Compliance of Personal Taxpayers (Case Study at the Regional Office of the Directorate General of Tax Office of West Java 1) - Larasati, Anissa Yuniar; Mardiani, Rika (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine the factors that influence the compliance of individual taxpayers at the Regional Office of the Directorate General of Taxation of West Java 1. There are four independent variables tested, namely the tax awareness factor, the fiscal attitude factor, the rational attitude factor and the tax law factor. While the dependent variable is personal taxpayer compliance. The sample method used is a purposive sample with a sample of 100 individual taxpayers for employees and non-employees. This study uses a multiple linear regression model with the help of SPSS v.21. This research method is quantitative, namely conducting primary data searches with the object of research of individual taxpayers who are registered in the Regional Office of DJP Jabar 1. tax, while tax officers and rational attitudes do not have a significant effect.